Entre le livre d’art et le livre d’artiste : de quelques catalogues hybrides - Aurélie Pignon (Appareil)
Art and books have a long history together. The artists’ books that appeared in the 1960s reshaped the uses of the work of art. In contrast, the book is a common object, a standardized commodity, a vehicle for reproductions that can itself be reproduced, a medium with diversified content. The aim of this article is to take a closer look at this concept by comparing it to the art book, especially to catalogs, to show the confusion it causes when being received. The two categories are opposed in their purpose—one being documentary, the other artistic—but are similar in the context in which they emerged: the art world, with its institutions, exhibitions, and performances. However, the variability of the notion of work of art raises questions about the value of design and reproductions, as well as the value of the discourse in artists’ books. The aim here is to show the limits of the “artists’ books” category, which explores all the possibilities offered by the book form and can therefore be neither exclusive, nor prescriptive or systematic.